Olympic Programme Commission. Report to the 117th IOC Session (2005)
Background In November 2002, the IOC Session in Mexico City approved the principle of a systematic review of the Olympic programme and mandated the Olympic Programme Commission to lead the process. One of the key missions of the Olympic Programme Commission has been to set up a regular and clearly defined process by which the Olympic Programme would be reviewed a fter each Olympic Games. Evaluation criteria In order to fulfill this mission, the Olympic Programme Commission developed a set of criteria to be used in assessing the strengths and weaknesses of each sport and the value that each sport adds to the Olympic Programme. Following consultation with the International Federations (IFs) and other key stakeholders, the final list of 33 criteria was proposed to the IOC Session, which approved it in August 2004 in Athens. Data collection In September 2004, a questionnaire reflecting these criteria was sent to the 28 summer Olympic Federations and to the five Recognised Federations selected by the Executive Board for further study. This questionnaire was developed in electronic format, accessible through the Internet. Completed questionnaires were returned to the IOC Sports Department in December 2004, which then had the responsibility to verify all responses and request further information or c larification where necessary. While efforts were made to clarify certain information, the Commission decided that it was not possible to include all of the data gathered through the questionnaire in the reports due to inconsistencies in some information and difficulties in making fair and verifiable comparisons with certain information. Please note that most information provided by the International Federations was accepted as presented. Data provided by the International Federations were supplemented with information provided by the IOC, IOC experts and partners. The IOC also commissioned studies of the press and television coverage of the Olympic Games 2004, Athens. These studies were conducted by external and independent companies, respectively Observer Group AB (International) and Sports Marketing Surveys Ltd (SMS). The Olympic Programme Commission reviewed all data and has been able to draw its conclusions from the following sources of information: - Completed questionnaires from the Federations - IOC experts` knowledge in areas of Broadcasting, Environment, Venues, Media and Costs - IOC-commissioned studies on press coverage conducted by Observer Group - IOC-commissioned studies on broadcast coverage conducted by SMS - Information gathered through the IOC Documentation Centre - Information gathered through the World Anti-Doping A gency - Information gathered through the past Organising Committees of the O lympic Games Sport s Observation Programme The Olympic Programme Commission also took into account the information gathered through the Sports Observation Programme that was conducted in 2004 and 2005 (including the Athens 2004 Olympic Games), for all the 28 summer Olympic Sports and the five sports governed by Recognised Federations. Report preparation A mix of quantitative and qualitative information was then gathered to assess the overall strengths and weaknesses of each sport and discipline. Following this information gathering, the Olympic Programme Commission appointed a small Working Group from amongst its members to undertake a first in-depth analysis of the data collected and prepare the first draft of the individual reports on the sports. The full Commission then met to further develop and refine the content and structure of the complete report. This complete report represents therefore the collective opinion of the members of the Olympic Programme Commission. Following the meeting of the Olympic Programme Commission, each International Federation was given the opportunity to review and comment on its own section in March/April 2005. The IOC received extensive, constructive feedback from the International Federations, some providing factual corrections and others providing clarification or explanatory comments. In the interest of openness, every effort was made to include as many comments from the International Federations as possible. Report format: This report is presented on an IF by IF basis , in alphabetical order of the International Federation acronym; the five Recognised Federations appearing after the 28 summer Olympic Federations. Please find in section II of this report, the template used for the sports report, which presents all the information sources used in each part of the report, as well as the benchmarks established by the Commission for the purpose of assessment. With regard to the summary found at the end of each report, in most cases, a quantitative assessment was made based on the numbers provided, but in other areas a qualitative assessment was made based on standards established by the Commission. The Commission has intentionally kept any such subjective assessments or opinions on each sport to a minimum and wherever possible used language that is consistent across all reports in order to maintain balance and fairness. For some specific elements (`gender equity in the IF governing bodies`, `athlete representation` and `anti-doping`), the Commission has not made any assessment, but nevertheless chose to include the facts available for the information of the reader. `Finance` also appears in each of the 33 summaries. Otherwise, the various report headings a re covered in the summary only if the information provided falls above or below the defined benchmarks.